Using lncRNA Sequencing to Reveal a Putative lncRNA-mRNA Correlation Network and the Potential Role of PCBP1-AS1 in the Pathogenesis of Cervical Cancer - Li, Linhan; Peng, Qisong; Gong, Min; Ling, Ling; Xu, Yingxue; Liu, Qiaoling (Frontiers in Oncology, 2021)
Background/Aims: Long non-coding RNA (lncRNA) plays an important role in many diseases, which participate in posttranscriptional regulatory networks in tumors. However, the function of major lncRNAs in cervical cancer are unclear. Therefore, the aim of this study was to construct a lncRNA-mRNA co-expression function network and analyze lncRNAs that might contribute to the pathogenesis of cervical cancer. Methods: Differentially expressed lncRNAs (DElncRNAs) and mRNAs (DEmRNAs) between 3 pairs cervical cancer tissues and adjacent mucosa were identified by lncRNA microarray analysis. LncRNA-mRNA correlation analysis and enrichment of functions were performed with DEGs. PCBP1-AS1 from correlation network was selected as a candidate. The PCBP1-AS1 expression was examined by qPCR, and K-M survival, clinicopathology analysis, GSEA and immune infiltration analysis of PCBP1-AS1 were implemented. Immune responses of PCBP1-AS1 expression in cervical cancer were analyzed using TIMER and western blot. PCBP1-AS1 expression was knocked down and over-expressed to evaluate its role in cell proliferation, migration and invasion. Results: 130 lncRNAs were significantly differentially expressed in cervical cancer patient samples compared with controls. Differentially expressed mRNAs in lncRNA-mRNA interaction network was involved in EMT process. Combined with K-M survival results, co-expression network revealed PCBP1-AS1 was significantly associated with OS of cervical cancer patients and clinicopathological parameter. Moreover, PCBP1-AS1 expression was not only significantly increased in cervical cancer specimens, but also associated with tumor stage, TNM and invasion. GSEA revealed that PCBP1-AS1 is closely correlated with cell biological function via the p53 and notch signaling pathway. Timer analysis revealed that the amount of NK cells and M2 macrophage decreased when PCBP1-AS1 expression was high, which was consistent with the western results of detection in clinical samples. Furthermore, in vitro experiments showed high expression of PCBP1-AS1 promoted cell proliferation migration and invasion. Conclusions: Transcriptomic and lncRNA-mRNA correlation analysis revealed PCBP1-AS1 plays a key role as an independent prognostic factor in patients with cervical cancer. The identification of PCBP1-AS1 as a new biomarker for cervical cancer could help expound how changes in immune environment promote cervical cancer development.